2014
DOI: 10.1103/physrevd.90.056001
|View full text |Cite
|
Sign up to set email alerts
|

Flavor symmetry based MSSM: Theoretical models and phenomenological analysis

Abstract: We present a class of supersymmetric models in which symmetry considerations alone dictate the form of the soft SUSY breaking Lagrangian. We develop a class of minimal models, denoted as sMSSM -for flavor symmetry-based minimal supersymmetric standard model, which respect a grand unified symmetry such as SO(10) and a non-Abelian flavor symmetry H which suppresses SUSY-induced flavor violation. Explicit examples are constructed with the flavor symmetry being gauged SU (2) H and SO(3) H with the three families t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 125 publications
1
37
0
Order By: Relevance
“…Thus, it is hard to simultaneously explain the observed Higgs boson mass and resolve the muon g − 2 anomaly if we consider CMSSM, NUHM1 or NUHM2, since in all these cases, the slepton masses are larger than 1 TeV. Recently, there have been several attempts to reconcile this apparent tension between muon g − 2 and the Higgs boson mass within the MSSM framework by assuming non-universal SSB mass terms for the gauginos [13,14] or the sfermions [15,16] at the GUT scale. Indeed, a simultaneous explanation of m h and muon g − 2 is possible [17] in the presence of t − b − τ Yukawa coupling unification condition [18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is hard to simultaneously explain the observed Higgs boson mass and resolve the muon g − 2 anomaly if we consider CMSSM, NUHM1 or NUHM2, since in all these cases, the slepton masses are larger than 1 TeV. Recently, there have been several attempts to reconcile this apparent tension between muon g − 2 and the Higgs boson mass within the MSSM framework by assuming non-universal SSB mass terms for the gauginos [13,14] or the sfermions [15,16] at the GUT scale. Indeed, a simultaneous explanation of m h and muon g − 2 is possible [17] in the presence of t − b − τ Yukawa coupling unification condition [18].…”
Section: Introductionmentioning
confidence: 99%
“…In this Section we provide a brief description of the sMSSM setup and its motivations [17]. We also describe at the end of this section a complete model based on SU (2) flavor symmetry that leads to sMSSM phenomenology at energies below the GUT scale.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we develop further the framework of flavor symmetry-based minimal supersymmetric standard model, sMSSM, suggested recently [17]. It will be shown that in this framework, which consists of seven phenomenological parameters that describe supersymmetry breaking, it is possible to explain the muon g − 2 anomaly and the Higgs boson mass simultaneously, along with the observed dark matter abundance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations